MORPHOLOGY OF BONE MARROW IN VISCERAL LEISHMANIASIS - Idris, Muhammad; Farid, Jamila; Gul, Nasreen (Journal of Ayub Medical College Abbottabad, 2018)
Background: Visceral Leishmaniasis (Kala Azar), a vector borne parasitic disease is endemic in many parts of the world including South East Asia. It is a chronic febrile ailment caused by Leishmania Donovani (LD). More than three hundred million people living in the endemic areas are at high risk and fourteen million are living with the disease. Methods: This prospective study was conducted on seventy-five patients over a period of twelve years at the department of Pathology Ayub Medical College Abbottabad, focusing on the morphology of bone marrow aspirate obtained from patients. The aspirate was smeared on glass slides, fixed with alcohol and stained with Giemsa stain. The microscopic examination of stained slides was carried out by the single microscopist to avoid the difference of opinion. The initial diagnosis was further confirmed by tow experienced microscopists. Results: A minor difference was observed in the number of male and female participants, 38 versus 37, with male to female ratio of 1.02:1. The majority of the patients were 1-15 years old. As much as 45.2% patients were 1-5 years old. In this age group, males were affected more than the females with male to female ratio of 1.4:1. Most of the patients belonged to district Battagram and Tor Ghar. Bone marrow aspiration was easy and the marrow aspirate was found having marrow fragments on naked eye examination in majority of the patients. Extrahistiocytic LD bodies alone were seen in 100%, extra and intrahistiocytic in 80% and intrahistiocytic alone in 33.3% patients. The parasite index was 1-5 to 1-10 in 53.4% and 26.6% patients respectively. Conclusion: Visceral Leishmaniasis is endemic in the study area. Bone marrow examination, although an invasive procedure, gives direct microscopic diagnosis of visceral Leishmaniasis and may be considered where indicated. Keywords: Visceral Leishmaniasis; Bone marrow aspirate; Kala Azar; Sandfly